The effect of organoclay contents on morphological characterization, mechanical and thermal properties of epoxidized natural rubber-50 toughened polyamide 6 nanocomposites - Nouparvar, Hamed (2014)
Nanocomposites consisting of polyamide 6 (PA6) matrix with epoxidized natural rubber-50 (ENR-50) and organoclay-modified montmorillonite (OMMT) were prepared by melt blending in a twin-screw extruder followed by injection molding. The influence of varying amounts (0-6 phr) of OMMT loadings on ENR-50 (10 wt.%) toughened PA6 nanocomposites was examined. Morphological characterizations and mechanical and thermal properties of the blend and nanocomposites were investigated. The addition of OMMT resulted in an increase in tensile strength and modulus, while impact strength and elongation at break reduced. Thermal study revealed no significant change in thermal properties with OMMT loadings. Exfoliated structure was observed from X-ray diffraction (XRD) patterns for <4 phr OMMT and was confirmed by transmission electron microscopy (TEM) images.